Tren Pengelolaan Pariwisata Alam Sebagai Destinasi Pariwisata Lokal - Nurul Nugraha; Asep kurniawan; Titi Kusmayanti; Sari Butar-butar (Jurnal Ilmiah Wahana Pendidikan, 2023)
Tourism is a journey undertaken by a person or group to visit a certain place within a certain period of time. As a country that has natural beauty, Indonesia offers several natural attractions, one of which is natural tourism. There are lots of natural attractions in Indonesia and most of them are located in mountainous areas. Even though it has a beautiful panorama, there are still many people who do not know the conditions and locations of natural tourist attractions. Through this research there are results regarding how to increase trends and how to manage nature tourism. In this article method using literature review method. Conducting a literature review is an analytical activity that can serve as a critique of scientific research that has been conducted on a particular subject. Literature reviews are obtained from several journal articles as data an